The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1507/endocrj.ej13-0141
|View full text |Cite
|
Sign up to set email alerts
|

Small proliferative adipocytes: identification of proliferative cells expressing adipocyte markers [Review]

Abstract: It has been thought that adipocytes lack proliferative ability and do not revert to precursor cells. However, numerous findings that challenge this notion have also been reported. The idea that adipocytes dedifferentiate to fibroblast-like cells with increasing cell number was reported in 1975. This possibility has been ignored despite knowledge gained in the 1990s regarding adipocyte differentiation. Several studies on proliferation and dedifferentiation of adipocytes have been published, most of which were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Adipocyte numbers in fat tissue can drastically change, depending on the physiological context 3 , 4 . During WAT hyperplasia, mature adipocytes, in addition to preadipocytes, arguably contribute to an increase in cell number, although mature adipocytes are post-mitotic terminally-differentiated cells 21 23 . Here using Tg mice with over-expression of p27 in mature adipocytes under the control of the aP2 promoter, we found that the WAT of Tg mice was similar to that of WT mice, both in weight and morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipocyte numbers in fat tissue can drastically change, depending on the physiological context 3 , 4 . During WAT hyperplasia, mature adipocytes, in addition to preadipocytes, arguably contribute to an increase in cell number, although mature adipocytes are post-mitotic terminally-differentiated cells 21 23 . Here using Tg mice with over-expression of p27 in mature adipocytes under the control of the aP2 promoter, we found that the WAT of Tg mice was similar to that of WT mice, both in weight and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been repeatedly suggested that proliferation of mature adipocytes may also be involved in adipose tissue hyperplasia. During WAT hyperplasia, isotope-labeled thymidine was incorporated not only into the preadipocyte fraction, but also, into the mature adipocyte fraction 21 23 , although they are possibly attributed to the coexisting of adipose stem cells in this fraction. Primary cultured adipocytes can proliferate even after differentiation 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Our present results showed that under extended hypoxic stress, incorporation of BrdU in human glioma U87-MG cells was repressed in concentration-and time-dependently. BrdU incorporation in cells can be measured to explain cell cycle processing in order to monitor the status of cell proliferation (35). Thus, this study demonstrated the suppressive effects of extended hypoxia on the proliferation of human glioma cells.…”
Section: Discussionmentioning
confidence: 71%
“…We previously identified SPA as a novel population of cells expressing both adipocyte-specific genes and proliferative activity in adipose tissue (Kajita et al 2013). In this study, we focused on the characteristics of SPA.…”
Section: Discussionmentioning
confidence: 99%